2023
DOI: 10.2186/jpr.jpr_d_22_00304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ceramic thickness, ceramic translucency, and light transmission on light-cured bulk-fill resin composites as luting cement of lithium disilicate based-ceramics

Abstract: Lithium disilicate, a reinforced pressable glass ceramic, is a popular option for large-defect restoration owing to its esthetic feature and promising strength [1,2]. Ceramic cementation is a critical issue for achieving restoration longevity [3]. Features such as the degree of conversion, mechanical properties, bond strength, working time, shade stability, restorative thickness, and retention form design are criteria for cement selection consideration [4][5][6][7]. A higher degree of conversion (DC) ensures l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…These CAD/CAM materials for endocrowns are available in HT and LT grades and offer different levels of optical translucency to achieve aesthetically pleasing tooth restorations. Previous studies have investigated the impact of ceramic translucency on the polymerization of resin-based cements by the light irradiation of ceramic [ 21 , 42 , 43 ]. Kuijper et al [ 21 ] examined the influence of lithium disilicate translucency at thicknesses of 4.0 mm and 7.5 mm on the degree of conversion of dual-cure resin cement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These CAD/CAM materials for endocrowns are available in HT and LT grades and offer different levels of optical translucency to achieve aesthetically pleasing tooth restorations. Previous studies have investigated the impact of ceramic translucency on the polymerization of resin-based cements by the light irradiation of ceramic [ 21 , 42 , 43 ]. Kuijper et al [ 21 ] examined the influence of lithium disilicate translucency at thicknesses of 4.0 mm and 7.5 mm on the degree of conversion of dual-cure resin cement.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggested that the translucency grade of the lithium disilicate glass did not affect the degree of conversion. Similarly, Chen et al [ 42 ] explored the effect of lithium disilicate glass translucency on the polymerization of dual-cure resin cement through 1 mm- and 2 mm-thick samples, finding no significant effect on the microhardness or degree of conversion. In line with these findings, the present study revealed that differences in the translucency of all the examined CAD/CAM materials affected the polymerization of the dual-cure resin cement immediately after light irradiation, with little or no influence on polymerization after aging.…”
Section: Discussionmentioning
confidence: 99%